Association of obesity, diabetes mellitus, and hypertension with dengue severity / Mohd Syis Zulkipli - Mohd Syis, Zulkipli (2019)
Dengue fever (DF) has unpredictable clinical progressions and outcomes. With the increasing prevalence of obesity, diabetes, and hypertension, these risk factors will likely play a more significant role in increasing the burden and mortality related to dengue infection. This study seeks to determine the association between obesity, diabetes, hypertension, and dengue severity (DS) in confirmed dengue cases among those aged 15 years and above in Malaysia’s primary health care setting. A cohort study was conducted in the central region of Peninsular Malaysia from May 2016 to November 2017. We collected demographic, clinical history, physical examination, and laboratory examination information. The exposures of interest were obesity, diabetes, and hypertension. DS was defined as either dengue with warning signs or severe dengue. Participants underwent daily follow-up during which we recorded their vital signs, full blood count, and random blood sugar (RBS) results. The prevalence and incidence of DS were modelled using multivariable and random intercept logistic regression. The changes in platelet and hematocrit levels were modelled using random intercept linear regression. The final model of obesity was adjusted for age, gender, and ethnicity. Similarly, the final model of diabetes and hypertension was adjusted for age, gender, ethnicity, and Body Mass Index (BMI) categories. Out of 362 dengue patients, 48.9% were diagnosed with DS at enrolment. Based on the association between obesity and DS, we found significant associations between: (i) BMI (kg/m2 ) and prevalence of DS (Adjusted Odds Ratio (aOR)=1.04; 95% Confidence Interval (CI):1.00,1.08; p=0.034); (ii) BMI (kg/m2 ) and incidence of DS (aOR=1.15; 95% CI:1.03,1.28; p=0.016); (iii) BMI (kg/m2 ) and hematocrit (%) (Adjusted Beta (aβ)=0.09; 95% CI:0.01,0.17; p=0.021); (iv) BMI (kg/m2 ) and changes in hematocrit (%) (aβ=0.07; 95% CI:0.003,0.15; p=0.041); (v) obese and iv hematocrit (%) (aβ=1.77; 95% CI:0.53,3.01; p=0.005); (vi) obese and changes in hematocrit (%) (aβ=1.39; 95% CI:0.25,2.53; p=0.017); (vii) waist circumference (cm) and changes in platelet (x103 /µL) at phase 3 of DF (aβ=0.84; 95% CI:0.24,1.45; p=0.006); and (viii) abdominal obesity and changes in platelet (x103 /µL) at phase 3 of DF (aβ=21.08; 95% CI:6.03,36.13; p=0.006). For the association between diabetes and DS, we found significant associations between: (i) RBS (mmol/L) among non-diabetes and incidence of DS (aOR=1.57; 95% CI:1.13,2.18; p=0.007); (ii) RBS (mmol/L) and platelet (x103 /µL) (aβ=-2.49; 95% CI:-4.83,-0.16; p=0.037); (iii) RBS (mmol/L) and changes in platelet (x103 /µL) at phase 2 of DF (aβ=-2.74; 95% CI:-4.93,-0.54; p=0.014); (iv) RBS (mmol/L) among non-diabetes and changes in platelet levels at phase 2 of DF (aβ=-4.53; 95% CI:-7.72,-1.34; p=0.005); (v) diabetes and incidence of DS at phase 1 of DF (aOR=20.89; 95% CI:1.08,403.96; p=0.044); and (vi) diabetes and changes in platelet (x103 /µL) at phase 3 of DF (aβ=44.29; 95% CI:21.28,67.30; p<0.001). In the association between hypertension and DS, we only found significant associations between hypertension and changes in platelet (x103 /µL) at phase 3 of DF (aβ=37.70; 95% CI:11.50,63.91; p=0.005). This is the first study that determines the associations between obesity, diabetes, hypertension and DS. These risk factors play an important role in risk stratifying dengue patients